A Comparison of Lymphoid and Myeloid Cells Derived from Human Hematopoietic Stem Cells Xenografted into NOD-Derived Mouse Strains (2023)
Humanized mice are an invaluable tool for investigating human diseases such as cancer, infectious diseases, and graft-versus-host disease (GvHD). However, it is crucial to understand the strengths and limitations of humanized mice and select the most appropriate model. In this study, we describe the development of the human lymphoid and myeloid lineages using a flow cytometric analysis in four humanized mouse models derived from NOD mice xenotransplanted with CD34+ fetal cord blood from a single donor. Our results showed that all murine strains sustained human immune cells within a proinflammatory environment induced by GvHD. However, the Hu-SGM3 model consistently generated higher numbers of human T cells, monocytes, dendritic cells, mast cells, and megakaryocytes, and a low number of circulating platelets showing an activated profile when compared with the other murine strains. The hu-NOG-EXL model had a similar cell development profile but a higher number of circulating platelets with an inactivated state, and the hu-NSG and hu-NCG developed low frequencies of immune cells compared with the other models. Interestingly, only the hu-SGM3 and hu-EXL models developed mast cells. In conclusion, our findings highlight the importance of selecting the appropriate humanized mouse model for specific research questions, considering the strengths and limitations of each model and the immune cell populations of interest. © 2023 by the authors.